2011
DOI: 10.1371/journal.pmed.1001044
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Highly Active Antiretroviral Therapy on the Survival of HIV-Infected Children in a Resource-Deprived Setting: A Cohort Study

Abstract: This observational cohort study by Andrew Edmonds and colleagues reports that treatment with highly active antiretroviral therapy (HAART) markedly improves the survival of HIV-infected children in Kinshasa, DRC, a resource-deprived setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
102
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 38 publications
10
102
2
3
Order By: Relevance
“…There is strong evidence that the early initiation of ART in HIV-infected children can substantially reduce HIV-related morbidity and mortality. [3][4][5][6] In the guidelines it published in 2010, the World Health Organization (WHO) recommended the immediate initiation of ART upon diagnosis of HIV infection in infants and older children, irrespective of the children's CD4+ T-lymphocyte counts. 7 The early initiation of ART in infants requires reliable early infant diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that the early initiation of ART in HIV-infected children can substantially reduce HIV-related morbidity and mortality. [3][4][5][6] In the guidelines it published in 2010, the World Health Organization (WHO) recommended the immediate initiation of ART upon diagnosis of HIV infection in infants and older children, irrespective of the children's CD4+ T-lymphocyte counts. 7 The early initiation of ART in infants requires reliable early infant diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…urrently available combination antiretroviral therapy (cART) for human immunodeficiency virus type 1 (HIV-1) infection and AIDS potently suppresses the replication of HIV-1 and significantly extends the life expectancy of HIV-1-infected individuals (1)(2)(3)(4). Recent analyses have revealed that mortality rates for HIV-1-infected persons have become close to that of general population and that the recent first-line cART with integrase inhibitors or boosted protease inhibitor (PI)-based regimens has made the development of HIV-1 resistance significantly less likely over an extended period of time (5,6).…”
mentioning
confidence: 99%
“…The availabilty and rapid scaling up of Antiretroviral Therapy (ART) programmes for infants and children with Human Immunodeficiency Virus (HIV) infection in Low-Middle Income Countries (LMIC) has enabled many to survive and grow into adolescents and adults [1][2][3]. However, retention in care of children and adolescents with HIV remains a major operational challenge requiring innovation and creativity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%